Molecular Dynamics-Based Two-Dimensional Simulation of Powder Bed Additive Manufacturing Process for Unimodal and Bimodal Systems - Yeasir Mohammad Akib; Ehsan Marzbanrad; Farid Ahmed (Journal of Manufacturing and Materials Processing)
The trend of adapting powder bed fusion (PBF) for product manufacturing continues to grow as this process is highly capable of producing functional 3D components with micro-scale precision. The powder bed’s properties (e.g., powder packing, material properties, flowability, etc.) and thermal energy deposition heavily influence the build quality in the PBF process. The packing density in the powder bed dictates the bulk powder behavior and in-process performance and, therefore, significantly impacts the mechanical and physical properties of the printed components. Numerical modeling of the powder bed process helps to understand the powder spreading process and predict experimental outcomes. A two-dimensional powder bed was developed in this work using the LAMMPS (Large-scale Atomic/Molecular Massively Parallel Simulator) package to better understand the effect of bimodal and unimodal particle size distribution on powder bed packing. A cloud-based pouring of powders with varying volume fractions and different initialization velocities was adopted, where a blade-type recoater was used to spread the powders. The packing fraction was investigated for both bimodal and unimodal systems. The simulation results showed that the average packing fraction for bimodal and unimodal systems was 76.53% and 71.56%, respectively. A particle-size distribution-based spatially varying powder agglomeration was observed in the simulated powder bed. Powder segregation was also studied in this work, and it appeared less likely in the unimodal system compared to the bimodal system with a higher percentage of bigger particles.